ROAD GEOMETRIC FEASIBILITY IN ROAD SAGARANTEN – TEGALBULEUD KM.BDG 175 + 100 - Paikun, Paikun; Andriani SP, Reffy W; Destaman, Faldi; Winardi, Dede (ASTONJADRO, 2021)
The Sagaranten-Tegalbuleud road is a provincial road, with its geographic and topographic conditions quite complicated, the terrain quite difficult, causing not all areas to be well connected, and the reason for the low level of accessibility of this area. Therefore, determining the road geometry is an important part of driving comfort. Geometric planning focuses on horizontal and vertical alignments so that it can fulfill the basic functions of the road that provide optimal traffic flow comfort according to the planned speed. A re-survey was conducted to obtain geometric data on existing roads that did not comply with DGH standards, then it was re-planned. The results of the analysis are three bends with the Spiral-Circle-Spiral type, namely bend 9, bend 10 and bend 11 with RC = 17 m, and the slope is determined for the vertical geometrical alignment of the road. The results of this research analysis can be used as a reference for improving geometric roads so that accessibility between regions can be increased.